Commodification of the Nyangku Traditional Ceremony in Panjalu of West Java - Mustakimah, Lina; Huriani, Yeni; Halim, Ilim Abdul (UIN Sunan Gunung Djati Bandung, 2024)
This research discusses the Nyangku traditional ceremony which has changed when viewed from a sociological perspective, namely the change in use value in the Nyangku traditional ceremony to exchange value which is called religious commodification, and this research will also explore the causes of this change using a sociology of religion approach. Types of research in this research is field research by collecting data based on the results of observations and interviews as well as documentation studies. This research concludes that the Nyangku traditional ceremony experienced religious commodification with the change from the use value of the Nyangku traditional ceremony to the exchange value as before Nyangku was the form of rituals of the Panjalu community, the cement of solidarity, social identity and efforts to care for the Panjalu ancestral heritage, become exchange values that have profit value in the form of promotions, sales of Nyangku symbols, as well as facilities that use tariffs provided for Nyangku. Then, the cause of the change from use value to exchange value at the Nyangku traditional ceremony occurred due to the existence of a charismatic figure who influenced the Panjalu community, the influence of religion, which provided a new perspective, and the Panjalu community's changing view of values.